The Role of Ambidextrous Organizational Culture and Psychological Safety in Shaping Innovative Work Behavior Among IT Sector Employees - Romulus, Marthin; Etikariena, Arum; Hilmi, Yusuf (Jayapangus Press, 2025)
Despite ongoing digital transformation efforts, Indonesia still lags behind in global innovation rankings, raising questions about the organizational and psychological factors influencing individual innovation in the IT sector. This study examines the role of Ambidextrous Organizational Culture (AOC) and Psychological Safety (PS) in shaping Innovative Work Behavior (IWB) among IT employees in Indonesia. Grounded in the Interactionist Perspective on Creativity, the study uses a quantitative approach with an online survey of 144 IT professionals. Validated instruments were used to measure AOC, PS, and IWB, with data analyzed using linear regression and Hayes' PROCESS Model 4. The findings show that AOC significantly predicts IWB both directly (β = 0.3973, p < 0.01) and indirectly through PS (indirect β = 0.2239), indicating a significant partial mediation effect. These results highlight the importance of cultivating a dual-focused organizational culture and psychologically safe environments to stimulate employee innovation. Practically, organizations should integrate cultural and psychological enablers into their HR and innovation strategies to strengthen innovative work behavior in Indonesia’s IT sector.